ET-04 Enhancing drug delivery with MRI-guided focused ultrasound for diffuse intrinsic pontine glioma model. (28th November 2020) - Ishida, Joji; Alli, Saira; Bondoc, Andrew; Fujita, Naohide; Kullervo, Hynynen; James, Rutka
Abstract: Diffuse intrinsic pontine glioma (DIPG) is surgically unresectable and one of the most devasting tumours in children. To date, there have been no effective chemotherapeutics against DIPG, despite a myriad of clinical trials. The intact blood-brain barrier (BBB) is partly responsible for the limited clinical response to chemotherapy. MRI-guided focused ultrasound (MRgFUS) is a promising non-invasive tissue ablation method for treating CNS tumours. Moreover, MRgFUS allows for temporary and repeatable BBB disruption. Our first objective was to determine the feasibility and safety of temporary BBB disruption within the brainstem using MRgFUS following intravenous administration of microbubbles in vivo. Our second objective was to select effective chemotherapeutics against DIPG cell lines, and to examine their therapeutic effects with MRgFUS in a murine model of DIPG which exhibits an intact BBB. Non-invasive opening of the BBB was determined in the brainstem of normal rodents using physiological monitoring and histological analysis. Doxorubicin was selected from a drug screen consisting of conventional chemotherapeutics tested against DIPG cell lines. We established SU-DIPG17 orthotopic xenografts which demonstrated diffusely infiltrative tumour growth. By LC-MS/MS analysis, MRgFUS led to a 4-fold increase in doxorubicin concentrations within the brainstem tumours as compared to controls. Moreover, the volumetric tumour growth rate was significantly suppressed in MRgFUS-treated animals, which also exhibited decreased Ki-67 expression. We demonstrated the feasibility and safety of MRgFUS in the rodent brainstem and have shown that MRgFUS increases doxorubicin uptake in the brainstem of a rodent model of DIPG. This preclinical data provides critical support for clinical trials investigating MRgFUS-mediated BBB opening, which may greatly improve chemotherapeutic efficacy against DIPG in children.